A Simple and Portable Screening Method for Adulterated Olive Oils Using the Hand‐Held FTIR Spectrometer and Chemometrics Tools. Issue 6 (22nd May 2018) - Pan, Meng; Sun, Suqin; Zhou, Qun; Chen, Jianbo
Abstract : Abstract: Extra virgin olive oil has been one of the most common targets for economically motivated food adulteration. This research employed the hand‐held FTIR spectrometer to develop the simple and portable screening methods for extra virgin olive oils adulterated with other cheaper vegetable oils. With the help of the ATR probe and chemometrics tools, oil samples can be measured directly without any pretreatment, then the spectra can be interpreted automatically to determine the possibility of adulteration and estimate the content of adulterant oil. A feasibility study of the hand‐held FTIR screening method was carried out using olive oils adulterated with canola oil, peanut oil, corn oil, soybean oil, and sunflower oil. The SIMCA model using the hand‐held FTIR spectra can identify different kinds of vegetable oils correctly and recognize olive oils with not less than 10% of adulterant oils. Meanwhile, the content of adulterant oil in the range of 5% to 45% can be estimated by the PLS model using the hand‐held FTIR spectra within an error of 3%. This research shows the potential of the hand‐held FTIR technique in the rapid and field screening of olive oils adulterated with some cheaper vegetable oils. Practical Application: This research provide a rapid and automatic detection method for olive oils adulterated with other cheaper vegetable oils. An oil sample can be measured directly within one minute, and the hand‐held instrument can be used anywhere needed.